An analysis towards legal challenges and strategic approaches in utilizing waqf real estate for sustainable food security - Mohd Yusoff, Rahmawati; Syed Abdul Kader, Sharifah Zubaidah; Arshad, Azhani; Halim, Akmal Hidayah; Rosli, Mohd Rilizam; Baharudin, Mohammad Hidir; Mohd Hafiz, Siti Mahfudzoh (Research & Scientific Innovation Society, 2025)
Issues relating to national food security is crucial, as Malaysia reported a food trade deficit rose to RM31 billion in 2022 as Malaysia fails to provide basic food for itself despite has lot of agro-food land. Hence, waqf real estate has a potential as a strategic asset for ensuring sustainable food security. However, inconsistent strategic management has reduced in utilizing waqf's real estates towards food security benefits. Therefore, this study examines the legal challenges associated with utilizing Waqf properties and proposes strategic approaches to enhance their efficacy in this context. The study employs a qualitative and descriptive cross- sectional analysis, utilizing existing legal frameworks and data obtained from relevant administrative bodies. This research research found that by integrating Islamic legal principles with modern sustainability practices, the research can provide a comprehensive framework for utilizing Waqf real estate in addressing food security concerns in Muslim-majority countries.